2011
DOI: 10.1103/physrevstab.14.090401
|View full text |Cite
|
Sign up to set email alerts
|

Highlights on photocathodes based on thin films prepared by pulsed laser deposition

Abstract: We review the current status of metallic photocathodes based on thin films prepared by pulsed laser deposition (PLD) and we explore ways to improve the performance of these devices. PLD seems to be a very efficient and suitable technique for producing adherent and uniform thin films. Time-resolved mass spectrometric investigations definitively suggest that the deposition of high-purity metallic thin films should be carried out in ultrahigh vacuum systems and after a deep and careful laser cleaning of the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…This value is in agreement with the value reported in literature for this material for a shorter wavelength [33] due to the fact that the photon energy at 355 nm is only a few tenths of eV over working function of Yttrium (3.0 eV), but lower than Copper (4.5 eV) [24]. Therefore, once found that the results reach the goal in terms of QE, a whole photocathode device with the design specifications required for an actual rf-gun shall be fabricated by using the lowest power density (in order to obtain a surface as smooth as possible).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This value is in agreement with the value reported in literature for this material for a shorter wavelength [33] due to the fact that the photon energy at 355 nm is only a few tenths of eV over working function of Yttrium (3.0 eV), but lower than Copper (4.5 eV) [24]. Therefore, once found that the results reach the goal in terms of QE, a whole photocathode device with the design specifications required for an actual rf-gun shall be fabricated by using the lowest power density (in order to obtain a surface as smooth as possible).…”
Section: Resultssupporting
confidence: 93%
“…The Cu films were deposited using a typical PLD system, described in a previous work [24]. Yttrium substrates were placed parallel to and in front of Cu targets of high purity (99.9%) at a distance of 5 cm, inside a high vacuum chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters are reported in Table 1. Equation (1) A detailed description of the experimental apparatus is described elsewhere [12], while the experimental conditions for the PLD thin film deposition are reported in Table 2. The films were grown at different substrate temperatures, ranging from 30 to 230 °C, by using an ohmic heater system.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The deposition of Y and Pb thin films was performed in a typical PLD high vacuum system described elsewhere [7]. Target and substrate were placed parallel inside the vacuum chamber, while the laser beam impinged at an angle of 45° on the target surface, provoking the ablation of the target and, thus, the deposition of the ablated material on the substrate surface.…”
Section: Experimental Set-upmentioning
confidence: 99%